PRACTICE OF NEUROMARKETING RESEARCH ON ARTWORK CONSUMPTION: LITERATURE REVIEW AND MARKETING MANAGEMENT PERSPECTIVE - CHALA, N.; PICHYK, K.; VOROPAI, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Nowadays there is a general understanding that we make most of our decisions on the unconscious level. Researchers continue asking people about their attitudes, emotions, and intentions, although not expecting to hear the whole truth. Under such circumstances, neuromarketing tools can significantly change our understanding of consumers and improve firms’ performance in the market.Gallery market being an important part of the country’s cultural heritage and tourist attractiveness, may suffer from excluding neuromarketing tools from the marketing management practice. Artworks are difficult to evaluate in terms of objective and measurable parameters. Therefore, people preferences towards a specific piece of art are hard to explain and distinguish during a standard marketing interview.The aim of this paper is to explore previous works, where researchers used neuromarketing to help them understand customer behavior of gallery visitors and artwork viewers. We review previous neuromarketing research works in gallery market, published during 2003-2020. In this paper, we generalize marketing problems that galleries try to solve with the help of neuromarketing tools. They mostly cover the aspects of customers’ attention, emotions, and artwork preferences.We suggest that neuroscience tools (fMRI and eye-tracking) can be beneficial for solving all three main types of marketing research problems – exploratory, descriptive, and causal. We also outline further perspectives in applying eye-tracking for solving marketing management issues in planning, problem solving and monitoring processes.
Keywords: Eye-tracking; emotions scanning; neuromarketing; galleries marketing; artwork